The benefits of information sharing in petroleum exploration : an R&D; approach to the study of the United Kingdom continental shelf - Barrera-Rey, F (Oxford Institute for Energy Studies, 1997)
This paper is an attempt to introduce information as an input in the production function of an exploration firm and apply this model to the study of the United Kingdom Continental Shelf (UKCS). This, almost trivial, observation to anyone acquainted with the workings of the exploration activity has been absent from economic-based models of exploration and it is our purpose to redress this balance by framing the analysis within the traditional R&D; framework.